Changes in beliefs of pre-service teachers in an ESP teacher education programme in Vietnam : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Palmerston North, New Zealand - Đặng, Thị Vân Anh (Massey University, 2019)
Pre-service English for Specific Purposes (ESP) teachers’ belief change has been under-researched, so little is known about how and why their beliefs change over their teacher education programs. This study aimed to identify beliefs about ESP teaching of pre-service teachers in an ESP teacher education programme in Vietnam; explore how their beliefs changed after the ESP teaching methodology course and after the practicum; and identify factors that influenced their belief changes. A qualitative case study approach and a multiple-case study design were employed to investigate the belief changes of twelve pre-service ESP teachers. Over a six month period, data were gathered through the employment of semi-structured interviews, reflective journals, observations, and stimulated recall interviews. These qualitative data went through two main analysis processes (within-case and cross-case analyses) and were analysed inductively, deductively, comparatively, and chronologically with the support of the NVivo software program. These comprehensive processes of data collection and analyses resulted in significant research findings. The findings revealed that the pre-service ESP teachers held a wide range of initial beliefs about ESP teaching before they were provided with theory and practice about ESP teaching. These initial beliefs, which originated from their ESP learning experiences in the teacher education programme, were found to have a number of distinctive features and were susceptible to change. The pre-service ESP teachers’ beliefs tended to change in six ways and follow two key processes of belief change. The findings also revealed a wide variety of contextual and internal factors that, despite playing different roles, exerted integrated influences on their beliefs. Therefore, this study highlights the importance of not only the ESP teacher education program but also the pre-service ESP teachers themselves in the development of their beliefs about ESP teaching. The findings from this study shed fresh light on the development of beliefs about ESP teaching of pre-service teachers in an ESP teacher education program. Insights into the complexity of their belief change processes will not only facilitate the development and improvement of ESP teacher education programmes in the future but also provide a basis for further research into this unexplored area.
Keywords: English language; Study and teaching; Foreign speakers; Vietnam; English teachers; Attitudes; 390307 Teacher education and professional development of educators